2017
DOI: 10.1038/srep40674
|View full text |Cite
|
Sign up to set email alerts
|

Methylation specific targeting of a chromatin remodeling complex from sponges to humans

Abstract: DNA cytosine methylation and methyl-cytosine binding domain (MBD) containing proteins are found throughout all vertebrate species studied to date. However, both the presence of DNA methylation and pattern of methylation varies among invertebrate species. Invertebrates generally have only a single MBD protein, MBD2/3, that does not always contain appropriate residues for selectively binding methylated DNA. Therefore, we sought to determine whether sponges, one of the most ancient extant metazoan lineages, posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…For comparison, we assessed mCA recognition by MBD2, which shows very high selectivity for mCG [16,24] and represents the most evolutionarily ancient MBD protein [25,26] (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, we assessed mCA recognition by MBD2, which shows very high selectivity for mCG [16,24] and represents the most evolutionarily ancient MBD protein [25,26] (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The residue-specific changes in the amide backbone of MeCP2 bound to the BDNF promoter sequences were monitored by 1 H/ 15 N-Heteronuclear Single-Quantum Correlation (HSQC) NMR spectroscopy and compared using standard chemical shift perturbations (CSPs). In NMR studies of the MBD family proteins, we identified linear chemical shift changes that correlate with methylated DNA binding and present in every ortholog and paralog examined to date [13,2628]. In particular, two of these resonances (Gly 27 and Ala 30 of MBD2) show large CSPs between the non-specific and methylation-specific binding modes, such that we have used these resonances as reporters of mCG binding [27].…”
Section: Resultsmentioning
confidence: 99%
“…These factors, when bound to methylated DNA, are capable of restricting the access for transcription factors causing downregulation of the gene expression [38]. Furthermore, members of MBD family proteins are capable of interacting with histone modification enzymes, promoting a more closed chromatin structure in order to restrict the access for the transcription machinery [39,40].…”
Section: Dna Methylationmentioning
confidence: 99%
“…A 28% knockdown of EmuGSK-3 for this experiment was confirmed with two internal replicates by qPCR, using EmuEf1-α as the housekeeping reference gene (Additional file 9 ). Though the RNAi technique as currently used in E. muelleri only results in knockdown of ~30% (range of ~20–50% depending on the gene tested), phenotypes of EmuGSK-3 knockdown sponges were distinct from those observed in other knockdown experiments targeting different genes [ 25 27 ].…”
Section: Resultsmentioning
confidence: 99%